Indian Capital Markets - A Road Ahead - Subha, M. V. (Indian Journal of Marketing, 2006)
The financial system of any country serves as a link to the savings of households with the investment objectives of firms, and plays a pivotal role in the allocation of economic resources among the surplus spending units and the deficit spending units. Capital markets serves as a link between the investors and the industry. Capital markets survive on information, which is made available through research and is reflected on the prices of shares. So, for a capital market to function efficiently, it is necessary that the information mechanism be in place. The current state of the India Capital Market is vibrant and very attractive to large number of foreign investors. The performance of the capital market in terms of number of transactions and volume of trade is quite impressive. We see the stock index values rising, and flow of funds from FII’s increasing. If we look at the profile of the investors investing in the markets, only a small proportion of retail investors are investing in the market. Majority of the investors still shy away from the market perceiving equity shares as risky investments. It is the role of the regulatory body of our country to restore confidence in the minds of the investors and induce them to invest in the Securities Market. This article looks into the current issues facing the Indian Capital Market and tries to analyze the prospect of the emerging Indian Capital market in the days to come. The article also tries to highlight the role played by SEBI in the development of the Indian Capital Market.